STRENGTHENING FINANCIAL GOVERNANCE THROUGH DIGITAL PAYMENT SYSTEMS FOR THE SUSTAINABLE GROWTH OF MSMES IN JEMBER CITY - Moh. Halim; Riyanto Setiawan Suharsono; Rendy Mirwan Aspirandi (PT. Antis International Publisher, 2026)
Objective: This study aims to examine the role of digital payment systems in strengthening financial governance and promoting sustainable growth among micro, small, and medium-sized enterprises (MSMEs) in Jember City. Method: The research employed a quantitative approach with a correlational design, involving 150 MSME respondents selected through purposive sampling, and utilized structured questionnaires based on a Likert scale. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models, including hypothesis testing and mediation analysis. Results: The results indicate that digital payment systems significantly enhance financial governance, which partially mediates the relationship between digital payment adoption and the sustainable growth of MSMEs. Novelty: These findings suggest that integrating digital payment technologies with effective financial governance mechanisms contributes to improved operational transparency, accountability, and long-term business sustainability, thereby offering theoretical, practical, and policy implications for MSMEs and relevant stakeholders.